Critical review of commissioning/routine tests with special interest in undetected defects in SF6, GIS/GITL using UHF method - Cebekhulu, Jabulani (My University, 2009)
The widespread application of pressurized SF6 gas and its mixtures as insulating medium in many electric power applications is the result of recent advances in technologies. The likelihood of failure for a Gas Insulated Substation or Transmission Line (GIS/GITL) is primarily due to the presence of defects inside the equipment. Defects can be introduced into the GIS/GITL system for various reasons. Partial discharge (PD) is a natural phenomenon occurring in the GIS/GITL systems, which invariably contains defects. During commissioning or routine tests PD measurements serve to identify the type and status of a defect. Of particular interest for this research work will be the critical review of PD measurement for different types of free conducting particles in the gas using the UHF method due to its superiority among others. The work highlights the integrity of the method as a tool for both commissioning and routine tests and its alignment with the high voltage SF6 test standards is reviewed. 80/20 N2/SF6 mixture is used to reduce the surface roughness effect in pure SF6, as well as for the reduction of economical and environmental risks.
Keywords: GIS/GITL; Inception voltage; Lift-off field; Partial discharge; UHF PD testing